NUMERICAL ANALYSIS OF NOX REMOVAL IN POLLUTED AT ATMOSPHERIC PRESSURE AND AMBIENT TEMPERATURE - ASKRI, S.; FEROUANI, A. K.; LEMERINI, M.; OUGHERB, C. (My University, 2018)
The aim of this work is to analyse the time evolution of the NOx species involved in a corona discharge used for NO pollution control in polluted air at atmospheric pressure and ambient temperature. The model takesin to account 20 chemical species (electrons, molecules N2, O2, H2O, CO2, OH, HNO3, CO, O3, atoms N, O, H, nitric oxides NO, NO2, NO3, N2O5, negative ions (O−,O−2,O−3) and metastable specie N(2D), in the mixture of a specific flue gas (N2: 76%, O2: 6%, H2O: 6% and CO2: 12%, and a few ppm of NO). These chemical species react following 100 selected chemical reactions. The density is analyzed by the continuity equation without diffusion term. We analyze the time evolution (10−9-10−3 s) of the density and the rate coefficient of certain reactions, under different reduced electric fields in the range of 50-300 Td .The obtained results show the contribution of N, O, OH radicals and N(2D) in reduction of NO and NO2. So, the NO removal efficiency reached 90% under 300 Td.
ICIME 2018 - International Conference in Integrated Management of Environment سوسة - تونس
Keywords: NUMERICAL ANALYSIS; NOx; POLLUTION; ATMOSPHERIC PRESSURE; AMBIENT TEMPERATURE